Abnormalities in pulmonary function in infants with high-risk congenital diaphragmatic hernia - Rygl, Michal; Rounova, Petra; Sulc, Jan; Slaby, Krystof; Stranak, Zbynek; Pycha, Karel; Svobodova, Tamara; Pohunek, Petr; Skaba, Richard (Biomedical papers, 2015)
Aims: The aim of the study was to analyze lung growth and abnormality of infant pulmonary function tests (IPFT) in congenital diaphragmatic hernia (CDH) survivors younger than three years of age with respect to unfavorable prognostic factors.Methods: Thirty high-risk CDH survivors at the age of 1.32±0.54 years, body weight 9.76±1.25 kg were examined using IPFT: tidal breathing analysis, baby resistance/compliance, whole baby body plethysmography and rapid thoraco-abdominal compression. Gore-Tex patch was used in 13% of patients (GORE group). Pulmonary hypertension was diagnosed and managed in 13% (iNO group). Standard protocols and appropriate reference values were used and obtained data were statistically analysed.Results: High incidence of peripheral airway obstruction (70%), increased value of functional residual capacity (FRCp) 191.3±24.5 mL (126.5±36.9 % predicted; P < 0.0005), increased value of effective airway resistance (Reff) 1.71±0.93 kPa.L-1.s (144.4±80.1 % predicted; P < 0.01) and decreased specific compliance of the respiratory system (Crs/kg) 14.1±2.3 mL.kPa.kg-1 (i.e., 76.1±20.1 % predicted, P < 0.0005) was noted in infants with CDH in comparison with reference values. Increased value of FRCp was found in GORE group (165.7±51.9 versus 120.4±31.2, P < 0.02) and in iNO group (183.1±52.6 versus 117.8±25.7 mL; P < 0.0005).Conclusion: A high incidence of peripheral airway obstruction, an increased value of FRCp and decreased specific compliance of the respiratory system was noted in infants with CDH. Unfavorable prognostic factors (Gore-Tex patch, pulmonary hypertension) correlate with more severe alteration of pulmonary function in infants.
Keywords: congenital diaphragmatic hernia; infant pulmonary function testing; lung dysfunction; chronic lung morbidity